REAKSI PASAR SAHAM PERUSAHAAN FARMASI SEBELUM DAN SESUDAH COVID-19 DI INDONESIA - Kartika Pradana Suryatimur; Nibras Anny Khabibah (Jurnal Aplikasi Akuntansi, 2021)
The COVID-19 pandemic has had an impact on social and economic activities that have an impact on stock market conditions in the world, including Indonesia. This study identified differences in stock prices and stock trading volumes (TVA) of companies in the pharmaceutical sector before and after the announcement of the first COVID-19 case in Indonesia. The sample used is 10 pharmaceutical sector companies listed on the Indonesia Stock Exchange (IDX). The method used in this research is an event study using paired sample t-test. Based on the test results, there was a difference in prices before and after the announcement of the first COVID-19 case in Indonesia, but there was no difference in trading volume testing.